Weathering-induced oxidation: An investigation of artificially aged polystyrene samples using Laser-induced Breakdown Spectroscopy. (August 2022) - Sommer, Caroline; Nguyen, Johnny; Menzel, Teresa; Prume, Julia A.; Ruckdäschel, Holger; Koch, Martin
Abstract: This study discusses weathering-induced oxidation of polystyrene with and without different concentrations of the antioxidant Irgafos using Laser-induced Breakdown Spectroscopy (LIBS). By examining the spectral feature of oxidation and due to laser ablation, a systematical analysis of the oxygen content on the sample's surface and its penetration depth could be conducted. The results show that LIBS can be used as a fast technique for the quantification of weathering-induced oxidation. Highlights: Spectroscopic characterization approach for weathering-induced oxidation. The study highlights LIBS' capability of surface and depth profile analysis. PS samples with different concentration of the antioxidant Irgafos have been artificially weathered for 200 h, 400 h, 800 h, 1400 h and 2000 h. Traces of weathering-induced oxidation could be measured from 400 h onwards.